Bacillus cereus var. Toyoi e Bacillus subtilis C-3102 em dietas para e alevinos de tilápia do Nilo, linhagem GIFT - Albuquerque, Daniele Menezes (2011)
The objective was to evaluate the water quality, performance, phenotypic sexing, corporal indexes, macro and micro composition, proximate composition, partial operating cost of Nile tilapia, GIFT strain, fed with diets formulated with probiotic Bacillus cereus var. Toyoi and Bacillus subtilis C-3102, during 113 days of cultivation in the sex reversal and nursery. Had been used 1200 post-larvae with an average initial weight of 24.7±0.50 mg. Fish were randomly distributed to a system of 24 aquaria of 0.03 m³ in a completely randomized design consisting of three treatments and eight replications, consisting of two probiotics and without probiotic. Initially during the sex reversal was considered an experimental unit, a aquarium containing 50 fish with a volume of 0.03 m³ and during the nursery an aquarium with 30 fingerlings. The data of performance, body índices, indexes, macro and micro composition, partial operation costs were subjected to ANOVA with 5% significance level, and sex ratio data were subjected to chi-square (χ2). There were differences (p<0.05) in the parameters of final weight, weight gain, average daily weight gain, specific growth rate, final biomass, biomass gain during sex reversal and nursery. Except for the specific growth, the fishes of nursery showed values of performance higher than sexual reversion. There was no association between the proportion of males and females (χ2=1.42, p=0.4926) and inclusion of the probiotics. There were no differences (p<0.05) in the indexes, proximate composition of the fishes fed with probiotics or absent in the rations. The inclusion of any of probiotics was influenced (p=0.00458) on calcium levels under carcass of the juveniles in relation to fish absent of probiotics. The COP was affected significantly (p=0.02159) for the treatment with Bacillus subtilis in its formulation in comparison to fish that were not fed probiotics. There was an increased colonization by bacteria and total coliforms during the nursery in relation to sex reversal (p<0.05). The utilization of the Bacillus subtilis and Bacillus cereus improves the performance and partial operating cost, and doesn t negatively affect the corporal indexes, intestinal microbiology, proximate composition, macro and micronutrients in the cultive fingerlings of Nile tilapia, GIFT strain.